2016
DOI: 10.1080/02726351.2016.1192570
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of gas–solid drag models in a bubbling fluidized bed

Abstract: Bubbling fluidized beds find application mainly in power conversion industries. For design, dimensioning and operation of fluidized bed equipment, the understanding of multiphase gas-solid flows is of great importance. The use of Computational Fluid Dynamics in the simulation of gassolid systems is limited by the complexity of mathematical models, which rely on a series of empirical or theoretical correlations. In the present work, the code MFIX was employed to simulate flows in a bubbling fluidized bed and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Luna et al 34 noted that the lattice Boltzmann method (LBM)‐based drag models provided better predictions compared to empirical drag models by accounting heterogeneous structures in the bubbling fluidization regime. Further, Zinani et al 23 found a significant difference in the instantaneous and time‐averaged results with different drag laws. In the above studies, simulations are conducted with 2D geometries to minimize the computation time with reasonable accuracy in predictions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Luna et al 34 noted that the lattice Boltzmann method (LBM)‐based drag models provided better predictions compared to empirical drag models by accounting heterogeneous structures in the bubbling fluidization regime. Further, Zinani et al 23 found a significant difference in the instantaneous and time‐averaged results with different drag laws. In the above studies, simulations are conducted with 2D geometries to minimize the computation time with reasonable accuracy in predictions.…”
Section: Introductionmentioning
confidence: 98%
“…A number of numerical studies were performed to study the effect of the drag model on flow predictions in various types of fluidized beds [7,12,[23][24][25][26][27][28]. Taghipour et al [7] conducted an experimental and computational study on a 2D gas-solid fluidized bed and observed that the Syamlal and O'Brien (SO) drag model shows a reasonable agreement for mean pressure drop, bed expansion, and gas-solid flow pattern.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of CFD in simulating gas–solid particle systems is still constrained by the complexity of mathematical models, which often involve a series of theoretical or empirical correlations. [ 6 ] In many cases, CFD may require the incorporation of additional mathematical models to achieve realistic system hydrodynamics. Upadhyay et al [ 7 ] applied artificial neural network (ANN) for predicting solid volume fraction along the riser height.…”
Section: Introductionmentioning
confidence: 99%
“…MFiX (which is an acronym for "Multiphase Flow with Interphase eXchanges") is developed by the National Energy Technology Laboratory of the United States. Presently, it is employed by researchers all around the world for various purposes [23][24][25][26][27][28][29][30][31][32]. We chose it because of its unique advantages: it is an open-source program that is entirely transparent to the user and editable, but it is also provided with a user-friendly graphical user interface (GUI).…”
Section: Introductionmentioning
confidence: 99%